Ending preventable child deaths from pneumonia and diarrhoea by 2025. Development of the integrated Global Action Plan for the Prevention and Control of Pneumonia and Diarrhoea. (22nd January 2015) - Qazi, Shamim; Aboubaker, Samira; MacLean, Rachel; Fontaine, Olivier; Mantel, Carsten; Goodman, Tracey; Young, Mark; Henderson, Peggy; Cherian, Thomas
Abstract : Despite the existence of low-cost and effective interventions for childhood pneumonia and diarrhoea, these conditions remain two of the leading killers of young children. Based on feedback from health professionals in countries with high child mortality, in 2009, WHO and Unicef began conceptualising an integrated approach for pneumonia and diarrhoea control. As part of this initiative, WHO and Unicef, with support from other partners, conducted a series of five workshops to facilitate the inclusion of coordinated actions for pneumonia and diarrhoea into the national health plans of 36 countries with high child mortality. This paper presents the findings from workshop and postworkshop follow-up activities and discusses the contribution of these findings to the development of the integrated Global Action Plan for the Prevention and Control of Pneumonia and Diarrhoea, which outlines the necessary actions for elimination of preventable child deaths from pneumonia and diarrhoea by 2025. Though this goal is ambitious, it is attainable through concerted efforts. By applying the lessons learned thus far and continuing to build upon them, and by leveraging existing political will and momentum for child survival, national governments and their supporting partners can ensure that preventable child deaths from pneumonia and diarrhoea are eventually eliminated.